Efficacy of perampanel for controlling seizures and improving neurological dysfunction in a patient with dentatorubral-pallidoluysian atrophy (DRPLA) - Shiraishi, Hideaki (Epilepsy Behav Case Rep, 2017)
We administered perampanel (PER) to a bedridden 13-year-old male patient with dentatorubral-pallidoluysian atrophy (DRPLA). The DRPLA diagnosis was based on the presence of a CAG trinucleotide repeat in the ATN1 gene. The patient experienced continuous myoclonic seizures and weekly generalized tonic–clonic seizures (GTCs). PER stopped the patient's myoclonic seizures and reduced the GTCs to fragmented clonic seizures. The patient recovered his intellectual abilities and began to walk again with assistance. We suggest that PER be considered as one of the key drugs used to treat patients with DRPLA.